Full-Duplex Mode in Amplify-and-Forward Relay Channels: Outage Probability and Ergodic Capacity - Rongyi Hu; Chunjing Hu; Jiamo Jiang; Xinqian Xie; Lei Song (International Journal of Antennas and Propagation)
This paper investigates the outage probability and ergodic capacity performances for full-duplex mode in two-way amplify-and-forward relay channels. The two-way relay channels which consist of two source nodes and a single relay node working in full-duplex mode, are assumed as independent and identically distributed as Rayleigh fading. The self-interference or loop interference of the relay is unavoidably investigated for full-duplex mode. And the close-form expressions for the outage probability and ergodic capacity of full-duplex mode are derived, considering both loop interference and the coefficients of two-way relay amplify-and-forward channels. To further facilitate the performance of full-duplex mode, the half-duplex modes over different transmission time slots are analyzed. Simulation results point out the effect of loop interference on outage probability and ergodic capacity of two-way amplify-and-forward relay channels with full-duplex mode and show that full-duplex mode can achieve better performance in terms of capacity and even outperform half-duplex modes in the presence of loop interference.